Resolving species boundaries in the critically imperiled freshwater mussel species, Fusconaia mitchelli (Bivalvia: Unionidae). (2nd September 2020) - Smith, Chase H.; Johnson, Nathan A.; Havlik, Kaitlyn; Doyle, Robert D.; Randklev, Charles R.
Abstract: Species are a fundamental unit of biology, and defining accurate species boundaries is integral to effective conservation and management of imperiled taxa. Freshwater mussels (Bivalvia: Unionidae) are among the most imperiled groups of organisms in North America, yet species boundaries remain uncertain for many taxa. The False Spike, Fusconaia mitchelli (Simpson in Dall, 1895), is a freshwater mussel considered to be endemic to central Texas (Brazos, Colorado, and Guadalupe drainages). Recent research revealed significant intraspecific genetic variation between geographically separated populations of F .  mitchelli, which could be indicative of speciation; however, small sample sizes for several of the populations precluded formal taxonomic revision. Here, we increase taxon sampling and use multilocus DNA sequence data and traditional morphometrics to re‐evaluate species boundaries in F .  mitchelli . We sequenced three loci: the protein‐coding mitochondrial DNA genes cytochrome c oxidase subunit 1 and NADH dehydrogenase 1, and the nuclear internal transcribed spacer 1 . Phylogenetic analyses depicted deep genetic divergence between F .  mitchelli in the Guadalupe and those in the Brazos and Colorado drainages, which was further supported by available biogeographic information. Morphometric analyses and coalescent‐based species delimitation models integrating both DNA sequence and morphological data provided strong support for the divergence observed between the two geographically isolated clades of F .  mitchelli . Based on these results, we revise taxonomy accordingly by elevating the junior synonym Fusconaia iheringi (Wright, 1898) to represent the Brazos and Colorado populations and restrict the distribution of F .  mitchelli to the Guadalupe River drainage. Our findings may impact pending management decisions to protect F .  mitchelli under the U.S. Endangered Species Act. Abstract : We conducted an integrative taxonomic assessment in the imperiled freshwater mussel species Fusconaia mitchelli . Molecular genetic analyses using mitochondrial and nuclear DNA sequence data, morphometric analyses, and species delimitation models integrating both molecular and morphological data provided strong support for the recognition of two species within F .  mitchelli . Based on these results, we revise taxonomy by elevating the junior synonym Fusconaia iheringi to represent the Brazos and Colorado drainages, and restrict F .  mitchelli to the Guadalupe drainage in central Texas.